Maintenance of Intestinal Homeostasis in Diarrhea-Predominant Irritable Bowel Syndrome by Electroacupuncture Through Submucosal Enteric Glial Cell-Derived S-Nitrosoglutathione - Hou, Yujun; Zhao, Ying; Jiang, Huiling; Wang, Kai; Zhang, Wei; Zhou, Siyuan; Li, Ying; Zheng, Qianhua (Frontiers in Physiology, 2022)
Objective. To determine whether electroacupuncture (EA) maintains intestinal homeostasis in IBS-D rats by repairing intestinal barrier function via EGC-derived GSNO. Methods. Sprague Dawley rats were randomly divided to a control group (n=10) and an IBS-D group (n=20), which received Senna solution by gavage and chronic unpredictable mild stress (CUMS) for 14 days and was further divided to a model group and an EA group. Rats in EA group were electroacupunctured at ST25 (Tianshu), ST36 (Zusanli), and LR3 (Taichong) for 20 min every day for 14 days. Abdominal withdrawal reflex (AWR), the percentage of time spent in open arms (OT%) in the elevated plus maze test and diarrhea index (DI) were measured. After rats were sacrificed, HE was performed to evaluate the pathological features of the colon. Transmission Electron Microscopy (TEM) was used to observe EGC in the muscle layer and submucosa layer. ELISA was used to detect the expression of GSNO in the colon, double immunofluorescence labeling was used to detect the colocalized expression of GFAP and GSNO in the muscle layer and submucosa layer. Plasma FITC-dextran was used to measure intestinal permeability and Western Blot (WB) was used to detect the expressions of ZO-1 and Occludin in the colon. Results. Compared with the control group, OT%, expressions of ZO-1 and Occludin were decreased significantly while AWR scores, DI, expression of GSNO in colon, colocalized expressions of GFAP and GSNO in submucosa layer, intestinal permeability were increased significantly and structural abnormalities of EGC were observed in the model group. After EA treatment, OT%, expressions of ZO-1 and Occludin were increased significantly, AWR scores, DI, expression of GSNO, colocalized expressions of GFAP and GSNO in submucosa layer, intestinal permeability were decreased significantly while the EGC structure was restored to normal. Conclusion. EA treatment downregulates the expressions of submucosal EGC-derived GSNO, repairs the intestinal barrier by upregulating the expressions of ZO-1 and Occludin, improves IBS-D symptoms including visceral hypersensitivity, anxiety and diarrhea, suggesting a potential role for EGC-derived GSNO in regulation of intestinal homeostasis in IBS-D rats.